Relationship between iron deficiency anemia and glycosylated hemoglobin in diabetes patients - Shnaigat, Saida Fuad; Abu Salma, Baha'a M. (Intelektual Pustaka Media Utama, 2025)
The study aimed to investigate the relationship between iron metabolism indicators such as ferritin and transferrin levels and glycosylated hemoglobin. Another goal of the current study is to draw the attention of the scientific and medical community to a very important issue regarding diagnostic and follow-up the diabetic patients which is the effect of iron status on HbA1c level. A cross-sectional study was conducted on (n=300) participants. The participant was assigned into three groups: the diabetes group (n=101), the prediabetes group (n=100), and the control group (n=99). A structured questionnaire with sociodemographic data and biochemical tests was applied. The results of the study found that there were significant differences in age among groups (p=0.05), with the diabetic group being younger than other groups. There is a direct positive relationship between HbA1c levels and ferritin (β=2%, p=0.001) and fasting blood sugar (β=1.8%, p=0.001). The findings also show an inverse relationship between glycosylated hemoglobin and transferrin (β=0.1%, p=0.001), as well as mean corpuscular volume (MCV) (β=1.8%, p=0.001). The study finding confirms a positive correlation between HbA1c with ferritin levels and a negative association with transferrin. Iron status in diabetes patients' treatment plans should considered while the interpretation of the HbA1c concentrations. In addition, diabetes patients' treatment plans should take ferritin level adjustment into account.